Molecular and cellular regulation of thermogenic fat - Wang, Cuihua; Wang, Xianju; Hu, Wenxiang (Frontiers in Endocrinology, 2023)
Thermogenic fat, consisting of brown and beige adipocytes, dissipates energy in the form of heat, in contrast to the characteristics of white adipocytes that store energy.Increasing energy expenditure by activating brown adipocytes or inducing beige adipocytes is a potential therapeutic strategy for treating obesity and type 2 diabetes. Thus, a better understanding of the underlying mechanisms of thermogenesis provides novel therapeutic interventions for metabolic diseases. In this review, we summarize the recent advances in the molecular regulation of thermogenesis, focusing on transcription factors, epigenetic regulators, metabolites, and non-coding RNAs. We further discuss the intercellular and inter-organ crosstalk that regulate thermogenesis, considering the heterogeneity and complex tissue microenvironment of thermogenic fat.